Analysis of Consumer Preferences Towards Products Ice Cream and Drink With Conjoine Method - Rosa Dwi Melati; Sumiati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – RD Ice Cream is an MSME that has been selling ice cream and boba. This study uses the conjoint method, a multivariate technique specifically developed to identify consumer preferences a wide array of products, services, or ideas. Design/methodology/approach – There are four attributes used in this study. That are flavor, toppings, packaging, and price. Then, ten combinations of attributes were offered to be assessed by 207 respondents. Findings – The results of the data analysis indicate that's the importance level of the products' attributes are the flavor of the ice cream (30,368), the flavor of the boba drink (38,196), the topping of the ice cream (20,699), the topping of the boba drink (14,435), the packaging of the ice cream (21,489), the packaging of the boba drink (18,229), the price of the ice cream (17,782), and the price of the boba drink (23,343). Further, the utility values demonstrate that, for ice cream category, consumers prefer chocolate flavor with oat-meal topping in 250 ml packaging at the price of IDR 15,000; while for boba drink consumers prefer the O'clock series flavor with other toppings than boba in 22 oz packaging at the price of IDR 10,000. Originality/value – This study applies conjoint analysis to identify priority product attributes for ice cream and boba drinks, offering new insights into how flavor, topping, packaging, and price combinations influence consumer preferences in a specific market context.